Family Business Sustainability Strategy In Sme Sector At West Sumatera Province - Dewi Mahrani Rangkuty; Alfian Zulmi (Ekopem: Jurnal Ekonomi Pembangunan, 2020)
The family company is a phenomenon in the business world. In addition to the numerous numbers, the family company also has a significant amount of the nation's economy. In Indonesia, for example, business people are dominated by a family company. Based on the results of the PWC survey in 2014 showed that more than 95% of businesses in Indonesia were family-owned and had a contribution of 25% of Indonesia's GDP. Small and medium industries in West Sumatera based on the 2018 BPS data amounted to 35. 592 Company and absorb 120,060 Labor. Micro and small companies totaled 108,588 companies and have absorbed 202,330 Labor. It is demonstrated that this sector is the largest sector that absorbs manpower in West Sumatera. Thus, it is necessary to formulate a family business resilience strategy in the MSME sector in West Sumatera. By using the analysis based on the study of literature that is formulated that to be able to grow, develop and endure in a long time SMEs actors need to 1) get the capitalization easy, safe and transparent, venture capital should be considered to be the main choice as a source of financing because it has a more "friendly" system and more suitable for SMEs entrepreneurs, 2) Pay attention, the understanding of SME entrepreneurs to institutional, human resources, accounting, networking, information technology and so forth will certainly be needed, 3) think of innovative marketing, where to be able to compete entrepreneurs need to create their own "blue ocean" market rather than having to compete in the "Red Ocean" market that nudges more bloody and have a lot of competitors, 4) always doing sustainable innovation, it becomes an important key for SMEs to survive, information technology developments and market uncertainty.